LECTURER PROFESSIONAL COMPETENCIES IN IMPROVING STUDENTS' MIND PATTERNS IN THE ERA OF DIGITALIZATION - Abdillah, Mahmudi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
Lecturers' professional competence in improving students' mindsets, namely evaluating the performance of lecturers who have the qualifications displayed in carrying out their obligations to provide educational services to the community. There are four lecturer competencies, namely (1) having knowledge about learning and human behavior; (2) have knowledge and mastery of the field of study they are studying; (3) have the right attitude about oneself, colleagues and the field of study one is developing; and (4) have technical teaching skills. The research method that the researcher will use is library research with a qualitative method, namely reviewing literature related to the professional competence of lecturers. Qualitative methods prioritize observing phenomena. There are two types of mindset, namely: First, Fixed Mindset. Second, Growth Mindset, namely a mindset (view) that can be developed through practice, training, appropriate ways/methods. The efforts to improve student mindsets, especially in this era of digitalization, are by motivating a mindset that continues to develop, not a mindset that remains in place. for example (1) Study and work, (2) Study will be a lifelong challenge. (3) Learning no longer has to be at school or university. (4) Educational institutions are slow to adapt. (5). Organizational awareness is needed to continue learning.